Ultra-high-strength geopolymer concrete influenced by mixture proportion and steel fiber: flowability, compressive strength, and flexural performance - Huang, Haonan; Yang, Liu; Jiang, Wen; Chen, Yu; Hou, Xianghua (Frontiers in Materials, 2026)
Ultra-high-performance geopolymer concrete is a low-carbon and environmentally friendly cementitious composite formed through alkali activation of industrial by-products and incorporation of ultrafine fillers and fiber reinforcement, exhibiting high compressive strength and excellent durability. In this study, ultra-high-strength geopolymer concretes (UHSGM) were prepared using ground granulated blast furnace slag (GGBFS), fly ash (FA), and silica fume (SF) as binders. Three GGBFS-to-FA mass ratios, namely 4:1, 1:1, and 1:4, were adopted. The SF content was varied at 0%, 5%, 10%, 20%, and 30% by mass of the precursor. In addition, three types of steel fiber were incorporated at a constant volume fraction of 2%. Two curing conditions, namely standard curing and steam curing, were adopted. The influences of mixture proportions, with or without silica fume and steel fiber, on the flowability, compressive strength, and flexural performance of UHSGM were systematically evaluated. The results indicated that an increase in GGBFS content led to a reduction in flowability but an enhancement in the compressive strength of UHSGM. The influence of SF on flowability and compressive strength was strongly dependent on the GGBFS-to-FA ratio. The highest compressive strength of the geopolymer reached 157.0 MPa at a GGBFS-to-FA ratio of 4:1 with 5% SF, which is comparable to that of ultra-high-performance concrete. An increase in GGBFS content and the incorporation of steel fibers enhanced the flexural strength of UHSGM, whereas high-temperature curing led to a reduction in flexural strength. An increase in SF had a negative effect on the deflection capacity and toughness of UHSGM, regardless of curing conditions. Further investigation is required to optimize the overall performance of UHSGM.